COMBINED ANTIHYPERTENSIVE THERAPY: ACE INHIBITOR PLUS CALCIUM CHANNEL BLOCKER. NEW ADVANTAGES OF THE KNOWN COMBINATION - S. A. Boitsov; R. M. Linchak (Рациональная фармакотерапия в кардиологии)
Advantages of combined therapy of patients with arterial hypertension are considered. Special attention is paid to usage of ACE inhibitor and calcium antagonist combination.